Ecosystem approach to assessing the effectiveness of socially oriented entrepreneurship - A.M. Dzhulaeva; В.Z. Nurmanova; M. Suleimenova; E.N. Sidorenko (Хабаршысы. Экономика сериясы)
The most pressing task of modern society is to ensure sustainable development based on inclusive economic growth. In this regard, the importance of social and socially oriented entrepreneurship in achieving the Sustainable Development Goals is increasing. Scientific research discusses various aspects of the phenomenon of social entrepreneurship. The least developed in the applied aspect is the issue of the effectiveness of social entrepreneurship and its assessment. The purpose of the study is to determine the conceptual foundations of the ecosystem approach to assessing the effectiveness of socially oriented entrepreneurship to improve the sustainability of the socio-economic development of regions.